Magnetic properties of macroscopic colloid crystals of silica-coated FePt nanoparticles with controllable interstices for molecular separation - Lo, C; Tsang, S; Yu, C; Tam, K (2009)
This paper reports on the magnetic properties of macroscopic colloidal crystals comprising silica-encapsulated FePt nanoparticles which assembled into three dimensional regular arrays by magnetic crystallization. The crystals have potential for magnetic separation of paramagnetic chemical or biochemical entities (e.g., proteins) by providing local magnetic fields at the interstitial sites to promote magnetic retention of the entities of interest. Structural characterizations by transmission electron microscopy and small angle x-ray scattering using a synchrotron source indicate a hcp arrangement of the nanoparticles in the colloidal crystals. The crystals have a large surface area (110.6 m2 g-1) and a sharp pore size of 15 nm which is adjustable by controlling the silica shell thickness. Under applied fields, the colloidal crystals display substantially stronger magnetic responses than the unaligned particle assembly, thus favoring removal of the colloidal crystals from the mixture by magnetic means after magnetic separation. The potential of the colloidal crystals for separating paramagnetic biological or chemical species is demonstrated in absorption experiments using two proteins with and without a paramagnetic center. © 2009 American Institute of Physics.